2010
DOI: 10.1186/1824-7288-36-71
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Adrenocorticotropic Hormone Stimulated Plasma Cortisol Levels Among Egyptian Autistic Children: Relation to Disease Severity

Abstract: BackgroundAutism is a disorder of early childhood characterized by social impairment, communication abnormalities and stereotyped behaviors. The hypothalamic-pituitary-adrenocortical (HPA) axis deserves special attention, since it is the basis for emotions and social interactions that are affected in autism.AimTo assess basal and stimulated plasma cortisol, and adrenocorticotropic hormone (ACTH) levels in autistic children and their relationship to disease characteristics.MethodsFifty autistic children were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
(50 reference statements)
4
35
4
Order By: Relevance
“…Curin et al (2003), for example, found that individuals with autism had significantly lower serum concentrations of cortisol, p < 10(−6), and significantly higher concentrations of adrenocorticotropic hormone (ACTH), p = .002, than control ageand sex-matched participants. This was corroborated by Hamza, Hewedi, and Ismail (2010) who found that autistic patients had lower plasma basal (p = .032) and stimulated cortisol (p = .04) and higher ACTH (p = .01) than controls. They also found that the child's severity score, based on the CARS score, correlated positively with ACTH (r = .71, p = .02) and negatively with measures of basal (r = −.64, p = .04) and stimulated cortisol (r = −.88, p < .001).…”
Section: Hormonessupporting
confidence: 80%
“…Curin et al (2003), for example, found that individuals with autism had significantly lower serum concentrations of cortisol, p < 10(−6), and significantly higher concentrations of adrenocorticotropic hormone (ACTH), p = .002, than control ageand sex-matched participants. This was corroborated by Hamza, Hewedi, and Ismail (2010) who found that autistic patients had lower plasma basal (p = .032) and stimulated cortisol (p = .04) and higher ACTH (p = .01) than controls. They also found that the child's severity score, based on the CARS score, correlated positively with ACTH (r = .71, p = .02) and negatively with measures of basal (r = −.64, p = .04) and stimulated cortisol (r = −.88, p < .001).…”
Section: Hormonessupporting
confidence: 80%
“…An increase in ACTH levels in people with autism is the most consistent result reported from studies of anterior pituitary hormones [3,4,6,10]. In functional imaging studies of the limbic system, which is the neural basis of emotions and social interactions, people with autism have been shown to have impaired circuitry in extinguishing fear responses [21].…”
Section: Discussionmentioning
confidence: 84%
“…With regard to the regulation of this system, the activity of the HPA axis has differed in study populations with ASD depending on factors such as individual patterns of sensory sensitivity or stress levels, specific stress paradigm, or type of parameter assessed (saliva or plasma) (Brosnan et al, 2009;Corbett et al, 2006Corbett et al, , 2008Corbett et al, , 2009Hamza et al, 2010;Jansen et al, 2006;Zinke et al, 2010). In typically developing individuals, cortisol levels fluctuate with a diurnal rhythm; these levels begin to increase before awakening, show a rapid rise from awakening over the next 30-45 min, and then fall throughout the day, reaching a low point during the normal sleep cycle, to rise again in preparation for awakening (Clow et al, 2010).…”
Section: Introductionmentioning
confidence: 98%